New constraints on UHT metamorphism in the Eastern Ghats Province through the application of mineral equilibria modelling and in situ geochronology - Korhonen, Fawna; Saw, A.; Clark, Christopher; Brown, M.; Bhattacharya, S. (Elsevier Science BV, 2011)
High Mg–Al granulites from the Sunki locality in the central portion of the Eastern Ghats Province record evidence for the high-temperature peak and retrograde evolution. Peak metamorphic phase assemblages from two samples are garnet + orthopyroxene + quartz + ilmenite + melt and orthopyroxene + spinel + sillimanite + melt, respectively. Isochemical phase diagrams (pseudosections) based on bulk rock compositions calculated in the chemical system Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–Fe2O3 (NCKFMASHTO) and Al contents in orthopyroxene indicate peak UHT metamorphic conditions in excess of 960 °C and 9.7 kbar. Microstructures and the presence of cordierite interpreted to record the post-peak evolution show that the rocks underwent decompression and minor cooling from conditions of peak UHT metamorphism to conditions of ~ 900 °C at ~ 7.5 kbar. In situ U–Pb isotope analyses of monazite associated with garnet and cordierite using the Sensitive High Resolution Ion Microprobe (SHRIMP) yield a weighted mean 207Pb/235U age of ca. 980 Ma, which is interpreted to broadly constrain the timing of high-temperature monazite growth during decompression and melt crystallization at ~ 900–890 °C and 7.5 kbar. However, the range of 207Pb/235U monazite ages (from ca. 1014 Ma to 959 Ma for one sample and ca. 1043 Ma to 922 Ma for the second sample) suggest protracted monazite growth during the high-temperature retrograde evolution, and possibly diffusive lead loss during slow cooling after decompression. The results of the integrated petrologic and geochronologic approach presented here are inconsistent with a long time gap between peak conditions and the formation of cordierite-bearing assemblages at lower pressure, as proposed in previous studies, but are consistent with a simple evolution of a UHT peak followed by decompression and cooling.